2023
DOI: 10.1007/s12663-023-01878-8
|View full text |Cite
|
Sign up to set email alerts
|

Various Treatment Modalities in COVID-19 Associated Facial Mucormycosis and the Need for its Surgical Management: A Systematic Review

Abstract: Introduction Mucormycosis emerged as a wildfire in post-covid-19 infected patients. Most frequently involved sites of mucormycosis are rhino-orbital, rhino-sinusal and rhino-orbito-cerebral. The hallmark sign of mucormycosis is tissue necrosis, which is often a late sign. The fatality rate of mucormycosis is 46% globally. Despite early aggressive combined surgical and medical therapy, the prognosis of mucormycosis is poor. Methods We searched the electronic database of PubMed, web of science, Embase, Scopus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…24 The coronavirus disease 2019 (COVID-19) pandemic is thought to have driven a spike in the incidence of mucormycosis, as at-risk populations (particularly diabetics) were treated with prolonged courses of immunosuppressing steroids. 25 A meta-analysis of management and outcomes of mucormycosis found significant 90-day mortality benefit with combined surgical debridement and antifungal therapy, compared to antifungals alone. 26 Similarly, a systematic review concluded that surgical debridement should be performed whenever feasible concomitant to antifungal therapy to best reduce mortality in COVID-19-associated cases of rhino-orbito-cerebral mucormycosis.…”
Section: Mucormycosismentioning
confidence: 99%
See 3 more Smart Citations
“…24 The coronavirus disease 2019 (COVID-19) pandemic is thought to have driven a spike in the incidence of mucormycosis, as at-risk populations (particularly diabetics) were treated with prolonged courses of immunosuppressing steroids. 25 A meta-analysis of management and outcomes of mucormycosis found significant 90-day mortality benefit with combined surgical debridement and antifungal therapy, compared to antifungals alone. 26 Similarly, a systematic review concluded that surgical debridement should be performed whenever feasible concomitant to antifungal therapy to best reduce mortality in COVID-19-associated cases of rhino-orbito-cerebral mucormycosis.…”
Section: Mucormycosismentioning
confidence: 99%
“…26 Similarly, a systematic review concluded that surgical debridement should be performed whenever feasible concomitant to antifungal therapy to best reduce mortality in COVID-19-associated cases of rhino-orbito-cerebral mucormycosis. 25 MMS could also have some utility in this regard. 23 Isavuconazole, a second-generation broad-spectrum triazole, has been shown to have a similar efficacy to liposomal amphotericin B and a favorable safety profile.…”
Section: Mucormycosismentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic sign of mucormycosis is tissue necrosis, which is often a late sign. The mortality rate of mucormycosis is 46% worldwide (6).…”
Section: Introductionmentioning
confidence: 99%